Voltage equalization circuit for retired batteries for energy storage applications - A.K.M. Ahasan, Habib; Mohammad Kamrul, Hasan; Shayla, Islam; Musse Mohamed, Ahmed; Azana Hafizah, Mohd Aman; Ashish, Bagwari; Sheroz, Khan (Elsevier Science, Ltd., 2022)
In this paper, an active equalization circuit based on resonant converter is presented. This equalization circuit has been proposed to equalize the direct cell-to-cell voltage in a string. All electrochemical energy storage devices are connected in series. Using this equalization circuit energy transfer from higher energy and charge capacitive cell to lower energy and charge cell in the string. All MOSFET switches are operated by complementary Pulse-Width Modulation (PWM) signal. The working principle of this equalization circuit like that of a switches-capacitor equalization circuit. In this circuit, a single Inductor (L) capacitor (C) energy carrier and bidirectional low voltage MOSFET switches are used so that it can recover maximum energy, reduce conduction loss, and improve the switching loss drawback, reduce the equalization time duration between two cells and achieved zero voltage gap. This equalization circuit is bidirectional and operates under the three modes, namely, charging, discharging, and relaxation mode. The proposed circuit details, the working principle, and the mathematical analyzes are presented. The simulation results are validated by the demonstration of an experimental prototype hardware testbed. The experimental results based on lithium-ion, lead–acid, and super-capacitor are presented. This equalization circuit is low cost and occupies little space with efficiencies of 96%, 94.2%, and 84.43% for Li-ion, lead–acid and super-capacitor respectively.